An Early-Onset Advanced Rectal Cancer Patient With Increased KRAS Gene Copy Number Showed A Primary Resistance to Cetuximab in Combination With Chemotherapy: A Case Report - Fang, Tian; Liang, Tingting; Wang, Yizhuo; Wu, Haitao; Liu, Shuhan; Xie, Linying; Zhang, Zhihao; Liang, Jiaying; Yao, Cheng; Tan, Yehui; Wang, Chang (Frontiers in Oncology, 2021)
Mutations in KRAS (codon 12/13), NRAS, BRAFV600E, and amplification of ERBB2 and MET account for 70%–80% of anti- epidermal growth factor receptor (EGFR) monoclonal antibody primary resistance. However, the list of anti-EGFR monoclonal antibody primary resistance biomarkers is still incomplete. Herein, we report a case of wild-type RAS/BRAF metastatic colorectal cancer (CRC) with resistance to anti-EGFR monoclonal antibody and chemotherapy. Initially, mutation detection in postoperative tumor tissue by using amplification-refractory mutation system polymerase chain reaction indicated wild-type RAS/BRAF without point mutations, insertion deletions, or fusion mutations. Therefore, we recommended combined therapy of cetuximab and FOLFIRI after failure of platinum-based adjuvant chemotherapy, but the disease continued to progress. Next generation sequencing analysis of the postoperative tumor tissue revealed that KRAS copy number was increased and detected SMAD4, RNF43, and PREX2 mutations. The patient’s overall survival was less than one year. This is the first case of advanced CRC with increased copy numbers of KRAS resistant to cetuximab and chemotherapy, which results in poor patient survival, and other mutated genes may be associated with the outcomes. Our findings indicate KRAS copy number alterations should also be examined, especially with anti-EGFR monoclonal antibody therapy in CRC, since it may be related with the primary resistance to these drugs.